2018
DOI: 10.1080/00918369.2018.1490576
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Disgusted With Queers, not Fearful of Them”: The Interrelationships Among Disgust, Gay Men’s Sexual Behavior, and Homonegativity

Abstract: Using a combination of personal reflections, published literature, and original empirical research, we argue that the disgust triggered by gay men's sexual practices (specifically, anal intercourse) is a critical, though overlooked, contributor to heterosexual men and women's homonegativity (i.e., negative attitudes and behaviors directed toward men who are or are perceived to be gay). We conclude our article by articulating several directions for future inquiry that we believe will advance current understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Sexual disgust motivates the avoidance of sexual partners and behaviors that can lead to negative biological repercussions (e.g., sex with genetic relatives). However, it has also been suggested that sexual stimuli and behaviors that transgress culturally normative conceptualizations of sexuality may trigger sexual disgust (Morrison et al, 2019). Likewise, it should be indicated that perceived vulnerability to disease (PVD; Duncan et al, 2009) correlates positively with pathogen disgust and sexual disgust (Tybur et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual disgust motivates the avoidance of sexual partners and behaviors that can lead to negative biological repercussions (e.g., sex with genetic relatives). However, it has also been suggested that sexual stimuli and behaviors that transgress culturally normative conceptualizations of sexuality may trigger sexual disgust (Morrison et al, 2019). Likewise, it should be indicated that perceived vulnerability to disease (PVD; Duncan et al, 2009) correlates positively with pathogen disgust and sexual disgust (Tybur et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The current study sample of TGNC individuals—a minority group often under attack at the individual level (e.g., bullying, social exclusion; Whittle, Turner, & Al-Alami, 2007) and structural level (e.g., military ban, bathroom legislation; Ahuja, Ortega, Belkin, & Neira, 2019; Spencer, 2019) – may provide evidence of an inverse association between marginalization and partnership benefits: the more marginalized a group is, the fewer partnership-related health advantages experienced in that group. This seems reasonable, as partnered members of marginalized groups may be more visible, and thus experience more discrimination related to public displays of affection, and more structural relationship barriers such as a lack of hospital visitation rights for sexual minority individuals as compared to heterosexual individuals (Knauer, 2012; Morrison, Kiss, Bishop, & Morrison, 2019). This may explain why partnership does not always relate to health among sexual minority individuals (Du Bois et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We also extended Crosby et al's work by using multiple regression (rather than simple correlations) to test for independent relationships between components of sexual disgust and homonegativity and establish whether sexual disgust predicts homonegativity independently of the possible effects of both participant sex and participant age. Further tests for links between sexual disgust and homonegativity are arguably important because they would provide further support for the proposal that disgust plays an important role in negative attitudes to homosexuals (Morrison et al, 2019) and, in doing so, strengthen the evidence base for the likely effectiveness of interventions for reducing homonegativity that focus on disgust.…”
Section: Introductionmentioning
confidence: 91%